2021
DOI: 10.1590/pboci.2021.048
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Polymorphism in the Gene Encoding Methylenetetrahydrofolate Dehydrogenase 1 (MTHFD1) 1958G>A with Orofacial Cleft

Abstract: Objective: To evaluate the possible association of a polymorphism in the gene encoding methylenetetrahydrofolate dehydrogenase 1 (MTHFD1), 1958G>A, with the susceptibility to orofacial cleft in an Indonesian population. Material and Methods: A total of 200 stored secondary biological samples from 30 cases of orofacial cleft and 170 unaffected controls were analyzed to determine the polymorphism status at base 1958. The analysis was conducted using the PCR-restriction fragment length polymorphism technique afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…On the basis of the initial searches, a total of 104 publications were retrieved from the source databases (Figure 1). After a detailed evaluation, 10 papers analyzing the associations between MTHFD1 1958G > A variant and NSCLP risk were included in the meta-analysis (Mills et al, 2008; Palmieri et al, 2008; Bufalino et al, 2010; Mostowska et al, 2010; Zhao et al, 2013; de Aquino et al, 2014; Murthy et al, 2014b; Nan et al, 2014; Wu et al, 2015; Auerkari et al, 2021). To determine the source of heterogeneity, a subgroup analysis based on ethnicity was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the initial searches, a total of 104 publications were retrieved from the source databases (Figure 1). After a detailed evaluation, 10 papers analyzing the associations between MTHFD1 1958G > A variant and NSCLP risk were included in the meta-analysis (Mills et al, 2008; Palmieri et al, 2008; Bufalino et al, 2010; Mostowska et al, 2010; Zhao et al, 2013; de Aquino et al, 2014; Murthy et al, 2014b; Nan et al, 2014; Wu et al, 2015; Auerkari et al, 2021). To determine the source of heterogeneity, a subgroup analysis based on ethnicity was performed.…”
Section: Resultsmentioning
confidence: 99%
“…However, the studies are not consistent in reporting the link between the MTHFD1 1958G > A variant and NSCLP. Some studies found a link between the 1958G > A variant and NSCLP (Mostowska et al, 2006; Boyles et al, 2008; Murthy et al, 2014b; Wu et al, 2015; Auerkari et al, 2021), while others found no link (Mostowska et al, 2006; Boyles et al, 2008; Palmieri et al, 2008; Mostowska et al, 2010; Zhao et al, 2013; de Aquino et al, 2014; Nan et al, 2014;).…”
Section: Discussionmentioning
confidence: 99%